The Effect of the Mathematical Puzzle Playing Method on the Subtraction Calculation Ability of Grade 1 Students at SDN 104202 Bandar Setia (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of the mathematical puzzle playing method on the subtraction calculation ability of first-grade students of SDN 104202 Bandar Setia. The type of research used is a quasi-experiment with a pretest-posttest control group design. The research subjects consisted of two classes, namely class IA as the control class (22 students) and class IC as the experimental class (22 students). The research instrument was a subtraction calculation ability test that has been tested for validity and reliability. The results showed that the average posttest score of both classes was 78.86 in the control class and 84.77 in the experimental class where there was a significant difference. The independent t-test of both classes showed a significance value of 0.000 < 0.05, so the hypothesis H0 was rejected and H1 was accepted. Thus, it can be concluded that the mathematical puzzle method significantly improved the arithmetic and subtraction skills of first-grade students at SDN 104202 Bandar Setia.